Comparison of dexamethasone, granisetron and haloperidol in prevention of postoperative nausea and vomiting following laparoscopic surgeries: A prospective, double-blinded study - Shikha Sharma; Gnanasekar N; Pranjali Kurhekar (Global Journal of Anesthesiology - Peertechz Publications, 2019)
Background: Laparoscopic surgeries are most commonly performed surgeries. However, they are associated with increased incidences of postoperative nausea and vomiting.  Aim: We aimed to compare the effectiveness of dexamethasone, haloperidol, granisetron in prevention of postoperative nausea and vomiting following laparoscopic surgeries.  Methods: We conducted a randomized, double-blinded study including 90 patients both males and females undergoing laparoscopic surgeries in a tertiary hospital over 18 months. The subjects were randomized into three groups. Group I Dexamethasone 8mg, Group II Granisetron 2mg, Group III Haloperidol 1mg (n=30 each group). The study drugs were administered intravenously immediately after intubation. Patients were observed every 4th hourly till 24 hours for incidence of nausea, vomiting, pain and sedation.  Results: Incidence of vomiting was significantly less in dexamethasone group (p=0.047) as compared to granisetron and haloperidol and was statistically significant (p<0.047).There was no significant difference in the incidence of vomiting between other two groups. All other parameters were comparable in all the groups.  Conclusion: Dexamethasone in the dose of 8mg significantly reduces incidence of vomiting in laparoscopic surgeries than haloperidol and granisetron.  Trial Registry: Clinical Trial Registry of India 2018/03/018324